Resolving a QTL complex for height, heading, and grain yield on chromosome 3A in bread wheat. (12th February 2021) - Martinez, Alba Farre; Lister, Clare; Freeman, Sue; Ma, Jun; Berry, Simon; Wingen, Luzie; Griffiths, Simon
Abstract: Crop height (Ht), heading date (Hd), and grain yield (GY) are inter-related in wheat. Independent manipulation of each is important for adaptation and performance. Validated quantitative trait loci (QTLs) for all three co-locate on chromosome 3A in the Avalon×Cadenza population, with increased Ht, Hd, and GY contributed by Cadenza. We asked if these are linked or pleiotropic effects using recombinant lines, and showed that Ht and Hd effects are independent. The Chinese Spring equivalent to the newly defined Ht interval contained a gene cluster involved in cell wall growth and displaying high levels of differential transcript expression. The Hd locus is larger and rearranged compared with the reference genome, but FT2 ( Flowering Locus T2 ) is of particular interest. The Hd effect acted independently of photoperiod and vernalization, but did exhibit seasonal genotype×environment interaction. Recombinants were phenotyped for GY in replicated field experiments. GY was most associated with Cadenza alleles for later Hd, supporting physiological studies using the same lines proposing that 'late' alleles at this locus increase spike fertility and grain number (GN). The work has uncoupled height from heading and yield, and shown that one of very few validated GY QTLs in wheat is probably mediated by phenological variation. Abstract : There are only three validated wheat yield QTLs. Here, one of them was genetically dissected. This showed that the physiological basis of the yield effect is likely to be phenological.